2020
DOI: 10.1177/0021998320954903
|View full text |Cite
|
Sign up to set email alerts
|

Experimental fatigue behavior of carbon/flax hybrid composites under tensile loading

Abstract: The aim of the present study is to investigate the mechanical behavior of carbon/flax hybrid composites under static and fatigue tensile loading. The failure characteristics and parameters used in the fatigue tests were deduced from the static ones. The effect of the applied stress level, hybridization and stacking sequences on the stiffness, hysteresis loops, dissipated energy and damping, were studied for a various number of cycles during fatigue tests. The Wohler S-N curves were constructed to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Bagheri et al 18 investigated the tensile fatigue performance of carbon/flax/epoxy under stress-controlled amplitude, showing significant improvement in fatigue strength compared with previous work on neat flax. Ben Ameur et al 19 studied the mechanical performance of carbon/flax composites under static and tensile fatigue loading, the study demonstrated that the increase of the carbon fiber volume fraction resulted in an increase in the fatigue performance and resistance of the hybrid composite. Manteghi et al 20 examined the compressive fatigue performance of hybrid glass/flax/epoxy thermographic and conventional testing, which both showed similar high cycle fatigue strength.…”
Section: Introductionmentioning
confidence: 99%
“…Bagheri et al 18 investigated the tensile fatigue performance of carbon/flax/epoxy under stress-controlled amplitude, showing significant improvement in fatigue strength compared with previous work on neat flax. Ben Ameur et al 19 studied the mechanical performance of carbon/flax composites under static and tensile fatigue loading, the study demonstrated that the increase of the carbon fiber volume fraction resulted in an increase in the fatigue performance and resistance of the hybrid composite. Manteghi et al 20 examined the compressive fatigue performance of hybrid glass/flax/epoxy thermographic and conventional testing, which both showed similar high cycle fatigue strength.…”
Section: Introductionmentioning
confidence: 99%
“…The use of hysteresis curves is an effective approach for investigating the fatigue damage mechanisms as reported by Ameur et al 27 Therefore, the stress-local strain values were recorded for each fatigue cycle during the following: 1 to 10, 20 to100, 100 to 1000, 1000 to 10,000, 10,000 to 100,000 and from 100,000 up to failure. The increment within each interval equal to the initial range value.…”
Section: Discussionmentioning
confidence: 99%
“…21,29,30 The stored elastic potential energy ( U p ) in the adhesive joint equal to the area under the loading (upper) curve of the hysteresis loop, Figure 5. 16,21,31 The U p and the U d can be calculated for any given cycle ( N ) by equations (3) and (4), respectively 21,27,30
Figure 4.Schematic of stress-strain hysteresis loop.
Figure 5.Terms and nomenclatures of the potential and dissipated energies calculations.
…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, for hybrid composite with carbon ply exterior (CPPC), cracks propagated rapidly in the carbon plies and buckled at pineapple leaf fibre layers leading to delamination in the region between the two fibres at the tension sides, as shown in Figure 8. Sezgin and Berkalp [182] reported higher impact resistance and high tensile strength whenever highstrength glass or carbon layers were placed as the outer and inner layers of the hybrid composite, respectively.…”
Section: Natural Fibre/carbon Fibre Reinforced Hybrid Compositesmentioning
confidence: 99%